Cognitive Insight, Clinical Insight, and Reasoning in Schizophrenia: A Pilot Study in a Forensic Setting. Issue 4 (7th August 2016) - Kuokkanen, Riitta; Lappalainen, Raimo; Repo-Tiihonen, Eila; Tiihonen, Jari; Aho-Mustonen, Kati
ABSTRACT: This pilot study of 20 chronically ill male inpatients with schizophrenia and a history of violence investigates the relationships between cognitive insight, clinical insight, reasoning, and symptoms in a forensic setting. The majority (75%) of the patients with schizophrenia made hasty decisions based on a small amount of information (the jumping-to-conclusion bias, JTC). In addition, the data suggested that the more information patients gather, the more clinical insight they have and the less distressed they are by their symptoms. However, neither cognitive nor clinical insight were found to be statistically significantly associated with symptoms. The Beck Cognitive Insight Scale (BCIS) showed low and nonsignificant correlations with JTC bias as well as with symptoms. We discuss the potential significance of JTC bias, and clinical and cognitive insight in treatment of forensic schizophrenia patients with a history of violence.